Poor knowledge and awareness of human papillomavirus and cervical cancer among adult females in rural Ghana - Ken-Amoah, Sebastian; Blay Mensah, Loretta Betty; Eliason, Sebastian; Anane-Fenin, Betty; Agbeno, Evans Kofi; Essuman, Mainprice Akuoko; Essien-Baidoo, Samuel (Frontiers in Tropical Diseases, 2022)
Cervical cancer (CC) continues to be a global burden, and a disease of public health interest, especially in low- and middle-income countries. This study explored the knowledge and awareness of human papillomavirus (HPV) infection and CC and the risk-behavioural characteristics of an adult female population in rural Ghana. A total of 274 women, aged 21 years and above were recruited through multi-stage sampling. A questionnaire was used to obtain data on their socio-demographic and socio-economic characteristics and assess their knowledge and awareness of HPV and CC through face-to-face interviews. In all, 187 (68.2%) participants had poor knowledge of HPV and CC with 87 (31.8%) having good knowledge. Only 18.2% and 48.9% of them had prior awareness of HPV infection and CC, respectively. Their primary source of information was the broadcast media (TV and Radio stations) (60.1%). Regarding risky lifestyle behaviours, the mean age at sexual debut was 18.52 ± 2.39 years, 82.8% have had more than one lifetime sexual partner, 81.0% were multiparous with 51.5% using oral contraceptives. Women with higher educational attainment (cOR = 0.41; 95%CI = 0.20-0.81), monthly income (cOR = 0.31; 95%CI = 0.10-1.02), and lifetime sexual partners (aOR = 0.46; 95%CI = 0.21-1.00) were less likely to have poor CC and HPV knowledge compared to their counterparts. In conclusion, adult females in the rural population have limited knowledge and awareness of HPV infection and CC with low CC screening. Intensive educational campaigns should be organised and spearheaded on multiple platforms by the Ghana Health Service and civil societies to sensitise and educate women, in the rural parts of the country, on CC and its related preventive measures.